Taming the Elephant : Politics, Government, and Law in Pioneer California - Orsi, Richard J.; Burns, John F. (Book collections on Project MUSE., 2003)
The final of four volumes in the 'California History Sesquicentennial Series', this text compiles original essays which treat the consequential role of post-Gold Rush California government, politics and law in the building of a dynamic state with lasting impact to the present day.